2011
DOI: 10.4489/myco.2011.39.2.071
|View full text |Cite
|
Sign up to set email alerts
|

Multi-loci Molecular Characterisation of Endophytic Fungi Isolated from Five Medicinal Plants of Meghalaya, India

Abstract: The phylogenetic relationships of the most dominant and morphologically cryptic endophytic fungal isolates from each of five selected medicinal plants, namely Potentilla fulgens, Osbeckia stellata, Osbeckia chinensis, Camellia caduca, and Schima khasiana of the biodiversity rich state of Meghalaya, were assessed with random amplification of polymorphic DNA and PCR-restriction fragment length polymorphism profiles. Sequencing of the internal transcribed spacer 1, small subunit rRNA and partial β-tubulin gene fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…However, absence of enzyme in the solid media does not confirm the enzyme activity for the particular strain. 7 In this investigation, FC2AP does not produce xylanase in agar plate method but it produced considerable amount of xylanases in liquid medium till 7 th day of incubation and after the stipulated day the production was declined. The endophytic fungal isolates exhibited typical growth characteristics in Sabouraud's Dextrose Broth (SDB) and Malt Extract Broth (MEB).…”
Section: L-4 Life Science Pharmaceuticalsmentioning
confidence: 69%
“…However, absence of enzyme in the solid media does not confirm the enzyme activity for the particular strain. 7 In this investigation, FC2AP does not produce xylanase in agar plate method but it produced considerable amount of xylanases in liquid medium till 7 th day of incubation and after the stipulated day the production was declined. The endophytic fungal isolates exhibited typical growth characteristics in Sabouraud's Dextrose Broth (SDB) and Malt Extract Broth (MEB).…”
Section: L-4 Life Science Pharmaceuticalsmentioning
confidence: 69%
“…9). However, it should be noted that the endophytic fungal isolates in the present study demonstrated cryptic morphological characteristics and as such have been referred to in this paper only by their isolate numbers and morphological identity [23].…”
Section: Resultsmentioning
confidence: 90%
“…DNA samples were stored at 4°C for immediate use and at -20°C for long-term storage. The primers ITS1 and ITS4 were used to amplify the internal transcribed spacer region (ITS) of the nuclear ribosomal RNA operon, including the 3′ end of the 18S rRNA, ITS1 region, the 5.8S rRNA gene; ITS2 region and the 5′ end of the 28S rRNA gene (Bhagobaty & Joshi, 2011b). The PCR reaction mixture comprised of 10 µL fungal DNA, 5 µL 10 × PCR buffer, 1.5 µL of 50 mM MgCl 2 , 1 µL of 10 mM dNTP, 0.25 µL Taq polymerase, 40 pM each of the forward and the reverse primers in a total reaction volume of 50 µL.…”
Section: Molecular Characterization Of Endophytic Fungimentioning
confidence: 99%
“…The PCR reaction mixture comprised of 10 µL fungal DNA, 5 µL 10 × PCR buffer, 1.5 µL of 50 mM MgCl 2 , 1 µL of 10 mM dNTP, 0.25 µL Taq polymerase, 40 pM each of the forward and the reverse primers in a total reaction volume of 50 µL. Reaction consisted of an initial denaturation of 94 °C for 5 min followed by thirty cycles of 94 °C for 1 min, 52 °C for 30 sec, 72 °C for 1 min, and final extension for 10 min (Bhagobaty & Joshi, 2011b). PCR was carried out in a GeneAmp 9700 Thermal Cycler (Applied Biosystems, Foster City, CA, USA).…”
Section: Molecular Characterization Of Endophytic Fungimentioning
confidence: 99%